Aware Food Choices: Bridging the Gap Between Consumer Knowledge About Nutritional Requirements and Nutritional Information - Tarabella, Angela; Burchi, Barbara; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This Brief provides a snapshot of the continuing debate in the food industry on how to bridge the gap between consumer knowledge of nutrition principles and the nutrition information system currently in place for labelling. Aware Food Choices: Bridging the Gap Between Consumer Knowledge About Nutrition and Nutritional Information examines the available literature on consumer understanding of nutritional information and comments on the current poor knowledge shown by consumers about nutrition principles. Another focus of this Brief is on the evolution of nutritional information in food labelling andcurrent regulations on nutritional claims and product facts. In reviewing attempts to improve the nutrition information system, this work points out that consumers must first understand the data provided in order to utilize the system to make healthy food choices. Therefore, any campaigns aimed at improving the information system must concentrate on consumer data understanding of nutrition principles and components as opposed to a sole focus on labelling upgrades.
Introduction -- Literature Analysis on Consumer Understanding of Nutrition Information -- Diet and Nutritional Requirements -- Factors Influencing Energy Balance: Estimation Methods -- Nutrition Fundamentals -- The Evolution of Nutrition Information -- Claims and Other Front of Package Information.
Keywords: Food science; Nutrition .; Food Science; Nutrition